2018
DOI: 10.1002/app.47052
|View full text |Cite
|
Sign up to set email alerts
|

A sorbitol‐based phase‐selective organogelator for crude oil spills treatment

Abstract: An efficient sorbitol‐based phase‐selective organogelator has been synthesized by an one‐step reaction between sorbitol and benzaldehyde with high yields up to 90%. The organogelator could gelate a wide range of oils with minimum gelation concentration ranging from 0.04 to 0.10 g/mL within 17 min. Besides, the self‐assembly mode of the organogelator in the oil phase was presented. The organogelator could self‐assemble in the oil phase through the hydrogen bonding and the π–π stacking interactions to form three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…A wide variety of oils were tested and minimum gelation concentrations of 0.04–0.10 g/mL were observed. Gelation was found to occur within 17 min of adding the powdered gelator to the oils [ 128 ]. In further studies, they found that the amount of water used in the experiment did not impact gel formation.…”
Section: Applications Of Sugar-based Lmwgsmentioning
confidence: 99%
“…A wide variety of oils were tested and minimum gelation concentrations of 0.04–0.10 g/mL were observed. Gelation was found to occur within 17 min of adding the powdered gelator to the oils [ 128 ]. In further studies, they found that the amount of water used in the experiment did not impact gel formation.…”
Section: Applications Of Sugar-based Lmwgsmentioning
confidence: 99%
“…This gelator can congeal high density crude oils having API 24 and 13.5 respectively at very low loading of <2.5 wt%. Hou and co‐workers have demonstrated the ability of sorbitol‐based gelator 133 to congeal crude oil layer from a biphasic mixture oil and water, when applied as powder . The gelation time was found to be short (10 min) and the process was unaffected by the presence of common salts such as NaCl or CuSO 4 .…”
Section: Application Of Psogs Without Carrier Solventmentioning
confidence: 99%
“…Hou and co-workers have demonstrated the ability of sorbitol-based gelator 133 to congeal crude oil layer from a biphasic mixture oil and water, when applied as powder. [76] The gelation time was found to be short (10 min) and the process was unaffected by the presence of common salts such as NaCl or CuSO 4 . The gels formed by the gelator 133 in variety of oils were strong enough to be scooped out from the aqueous phase.…”
mentioning
confidence: 94%
“…Frequent marine oil spills and the illegal discharge of oily wastewater have resulted in irreversible damage to the aquatic ecosystem and huge economic losses. The conventional treatments for oil spills involve in situ combustion, biodegradation, dispersion, adsorption, and solidification, whereas, the corresponding consumption is huge. Therefore, researchers have paid considerable attention to developing environmentally friendly and efficient methods for dealing with oil spills. Phase-selective organogelators (PSOGs) have recently attracted more attention because of their advantages in handling oil spills. PSOGs can self-assemble to form a three-dimensional network structure by noncovalent interactions, such as hydrogen bonding, hydrophobic interactions, van der Waals forces, π–π interactions, and electrostatic interactions, which endow PSOGs with the capacity to immobilize the oil phase. With additional research, the service conditions of PSOGs are becoming more straightforward and more convenient. , However, these methods for the subsequent treatment of reclaimed organic gels are still more complicated. , Hence, it is necessary to develop a simple and efficient method for the separation and recovery of the oil phase and organogelators.…”
Section: Introductionmentioning
confidence: 99%